2019
DOI: 10.2147/ott.s189521
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNA-505 suppresses gastric cancer cell proliferation and invasion by directly targeting Polo-like kinase-1</p>

Abstract: PurposeThe expression of microRNA-505 (miR-505) has been investigated in various cancers; however, its effect and mechanism in relation to gastric cancer (GC) are yet to be determined. Thus, the current evaluation aimed to examine the expression and potential role of miR-505 in GC.Materials and methodsQuantitative real-time PCR was carried out to analyze miR-505 expression in GC cells and tissues. We observed that miR-505 is differentially expressed in GC cells following transfection of its mimics or inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…11 Abnormal expression of miR-505 has been observed in various cancers. Dang et al 12 found that miR-505 had some connections with GC cell proliferation and invasion. Zhong et al 13 pointed out that miR-505 functioned as a tumor suppressor in RCC by downregulating high mobility group box-1 protein (HMGB1).…”
mentioning
confidence: 99%
“…11 Abnormal expression of miR-505 has been observed in various cancers. Dang et al 12 found that miR-505 had some connections with GC cell proliferation and invasion. Zhong et al 13 pointed out that miR-505 functioned as a tumor suppressor in RCC by downregulating high mobility group box-1 protein (HMGB1).…”
mentioning
confidence: 99%
“…EMT is a great contributor to the CC cell chemotherapy and radiotherapy resistance; thus, inhibiting EMT improves the survival rate of CC patients by sensitizing the CC cells to radiotherapy and drugs [ 32 ]. The miR-505 mimic elevated N-cadherin expression but decreased E-cadherin in gastric cancer cells [ 38 ]. miR-505-5p was correlated with metastasis, and the overexpression of miR-505-5p inhibited metastasis and EMT in CC cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…EMT contributes to chemotherapy and radiotherapy resistance of CC cells, thus inhibiting EMT sensitizes CC cells sensitive to radiotherapy and drugs, and improves the survival rate of CC patients [32]. miR-505 mimic elevated Ncadherin expression but decreased E-cadherin in gastric cancer cells [36]. miR-505-5p was correlated with metastasis, and overexpression of miR-505-5p inhibited metastasis and EMT in CC cells [37].…”
Section: Discussionmentioning
confidence: 99%